ANALISIS EFEK DIGITAL CULTURE TERHADAP HOLISTIC WORK ENGAGEMENT GENERASI MILENIAL SEMASA COVID-19 - Nopriadi Saputra; Farhan Fitt Fanani; Engkos Achmad Kuncoro (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- This article intends to examine holistic work engagement of millennial employees who work in offices, as well as examine the influence of digital culture on work engagement in DKI Jaya during COVID-19. This article is based on a cross-sectional and quantitative-causal study by using a non-probabilistic sampling approach. Respondents are the first and second layers of the personal and professional network of the research team. They all live and/or work in Central Jakarta. The data from 399 office millennial employees were structured by utilizing PLS-SEM and processed with SmartPLS version 3.3. The results show that digital culture has a direct positive and significant effect on the four aspects of holistic work engagement. However, when the analysis tried to examined further, it turns out that the influence of digital culture is multi-layered, where at first it directly affects on physical engagement and then indirectly affects intellectual and emotional engagement, and finally impact on spiritual engagement. The development of digital culture is effective enough to be applied for engaging millennial employees holistically during this COVID-19 pandemic. Keywords: Holistic Work Engagement; Learning Culture; Millennials